Analisis Indeks Keragaman Hasil Tangkapan pada Rumpon Berbasis Sumberdaya Lokal di Perairan Kuala Daya Kabupaten Aceh Jaya - Melisa Rahayu; Muhammad Rizal; Hafinuddin Hafinuddin; Samsul Bahri; Ikhsanul Khairi; Afdhal Fuadi; Mursyidin Zakaria; Muhammad Ali Sarong (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2023)
FADs is an instrument that function as a place to gathered fish, so that make it easier for fisherman to find fish. This study aims to determine the diversity index, dominance and weight and length of the catch on local resources. The result of this study are expected to provide information on the types of fish caught using hand line the research was conducted from August to December 2022 in the waters of Kuala Daya, Aceh Jaya Regency. Data collected in the form of data on the number of fish (tail), weight (gr), length (cm). The data collection method used was experimental fishing for 4 trips at two observation stations. During the study the number of catches obtained was 14 fish consisting of 1 phylum (chordata), 1 class (actonopterygii), 1 order, 4 families and 7 species, while the fish species are malabar trevally (Carangoides malabaricus), yellowtail scad (Atule mate), yellowstripe scad (Selaroides leptolepis), orange spotted grouper (Ephinephelus coioides), moontail bullseye (Priachantus hamrur), malabar blood snapper (Lutjanus malabaricus), narrow barred Spanish mackerels (Scomberomorus commerson). The result showed that the diversity index values on FADs 1 and FADs 2 were 1.33 and 1.21 which were included in the relatively medium criteria. The dominance index values on both FADs are 2 and 2 which are included in the relatively high criteria, and the weight of fish caught on both FADs is 2.72 kilogram and 1.91 kilogram and the average length of fish caught on both FADs ranges from 14,4 cm – 40,25 cm and 20,9 – 40,5 cm.